P2 receptors, platelet function and pharmacological implications - Gachet, Christian (Thrombosis and Haemostasis, 2008)
ADP and ATP play a crucial role in platelet activation and their receptors are potential targets for antithrombotic drugs. The ATP-gated cation channel P2X1 and the two G protein-coupled ADP receptors, P2Y1 and P2Y12, selectively contribute to platelet aggregation and formation of a thrombus.Owing to its central role in the growth and stabilization of a thrombus, the P2Y12 receptor is an established target of antithrombotic drugs like the thienopyridines clopidogrel or prasugrel, or competitive antag-onists such as cangrelor or AZD6140.The optimal inhibition of this receptor to reach clinical efficacy while preserving patients from unacceptable bleeding is a matter of debate. On the other hand, studies in P2Y1 and P2X1 knockout mice and using selective P2Y1 and P2X1 antagonists have shown that these receptors are also attractive targets for new antithrombotic compounds. Finally, the regulation by the P2 receptors of the platelet involvement in inflammatory processes is also briefly discussed.
Keywords: Haemostasis; thrombosis; ADP; P2Y1; P2Y12; P2X1; antiplatelet drugs; thienopyridine; clopidogrel; prasugrel; AZD6140; cangrelor